2015
DOI: 10.1177/1932296815596760
|View full text |Cite
|
Sign up to set email alerts
|

Multisite Study of an Implanted Continuous Glucose Sensor Over 90 Days in Patients With Diabetes Mellitus

Abstract: Background: Continuous glucose monitoring (CGM), which enables real-time glucose display and trend information as well as real-time alarms, can improve glycemic control and quality of life in patients with diabetes mellitus. Previous reports have described strategies to extend the useable lifetime of a single sensor from 1-2 weeks to 28 days. The present multisite study describes the characterization of a sensing platform achieving 90 days of continuous use for a single, fully implanted sensor. Method: The Sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 25 publications
0
20
0
1
Order By: Relevance
“…This last category of optical sensing technique has been recently successfully applied by Senseonics (Senseonics, Inc., Germantown, MD, USA) to develop a fully implanted CGM system [22,53], the Eversense sensor, which provides real-time glucose measurements through the external coupled transmitter for an expected lifetime of six months [54]. Currently, the Eversense CGM is approved to be used in European countries only (CE mark received in 2016) with a lifetime of 90 days and an accuracy of 11.4% MARD [55]. While biocompatibility and patient acceptance of the new fully implanted technology remain key issues, lifetime and ease of use are the fundamental strengths of this approach.…”
Section: Technological Trends and Challenges For The Next Generation mentioning
confidence: 99%
See 1 more Smart Citation
“…This last category of optical sensing technique has been recently successfully applied by Senseonics (Senseonics, Inc., Germantown, MD, USA) to develop a fully implanted CGM system [22,53], the Eversense sensor, which provides real-time glucose measurements through the external coupled transmitter for an expected lifetime of six months [54]. Currently, the Eversense CGM is approved to be used in European countries only (CE mark received in 2016) with a lifetime of 90 days and an accuracy of 11.4% MARD [55]. While biocompatibility and patient acceptance of the new fully implanted technology remain key issues, lifetime and ease of use are the fundamental strengths of this approach.…”
Section: Technological Trends and Challenges For The Next Generation mentioning
confidence: 99%
“…Currently available CGM systems already incorporate smart features, such as alerts and alarms generation in case of hypoglycemic or hyperglycemic events, incorporation of glucose trend information, detection of sensor faults and artifacts [55,56]. Next generation systems certainly need to incorporate these features and to deal with data management and integration into external devices, e.g., smartphone apps or dedicated cloud platforms.…”
Section: Technological Trends and Challenges For The Next Generation mentioning
confidence: 99%
“…1,2 While recent studies of implanted SQ sensors have shown promising results, there is still much room for improvement, including the reduction of encapsulation-induced sensor lag. 3,4 We present a proof-of-concept study of a novel flushing assembly to routinely clean the sensor surface, thereby prolonging its lifetime. Placing the sensor in the intraperitoneal (IP) space allows flushing with saline that would not be possible in the restricted SQ space.…”
Section: Letter To the Editormentioning
confidence: 99%
“…3,4 We present a proof-of-concept study of a novel flushing assembly to routinely clean the sensor surface, thereby prolonging its lifetime. Placing the sensor in the intraperitoneal (IP) space allows flushing with saline that would not be possible in the restricted SQ space.…”
mentioning
confidence: 99%
“…9,10 Implantable CGM systems can provide the patient additional ease of use because no sensor is inserted through the skin, and consequently the transmitter can be removed easily and more frequently without the need for sensor replacement. Furthermore, the hassle of weekly sensor replacement with warm-up time and the risk of damage to the inserted sensor is reduced.…”
Section: Cgm Technology and Directions For Future Developmentmentioning
confidence: 99%